2002
DOI: 10.1103/physrevlett.89.286602
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasharp Magnetization Steps in Perovskite Manganites

Abstract: We report a detailed study of steplike metamagnetic transitions in polycrystalline Pr0.5Ca0.5Mn0.95Co0.05O3. The steps have a sudden onset below a critical temperature, are extremely sharp (width <2x10(-4) T), and occur at critical fields which are linearly dependent on the absolute value of the cooling field in which the sample is prepared. Similar transitions are also observed at low temperature in non-Co doped manganites, including single crystal samples. These data show that the steps are an intrinsic prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
166
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(192 citation statements)
references
References 28 publications
22
166
1
3
Order By: Relevance
“…It has been reported that many manganites show multiple steps with reduction in temperature. [14][15][16][17][26][27][28] The M-H curves were also recorded without thermal cycling. Figure 5 shows the two loop magnetization isotherms for Ce͑Fe 0.975 Ga 0.025 ͒ 2 without thermal cycling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that many manganites show multiple steps with reduction in temperature. [14][15][16][17][26][27][28] The M-H curves were also recorded without thermal cycling. Figure 5 shows the two loop magnetization isotherms for Ce͑Fe 0.975 Ga 0.025 ͒ 2 without thermal cycling.…”
Section: Resultsmentioning
confidence: 99%
“…11 Interestingly, single-step and multistep magnetization behaviors are observed in some mixed-valent manganites showing colossal magnetoresistance ͑CMR͒, even in polycrystalline form. [12][13][14][15][16][17][18][19][20] Basically, these materials are phaseseparated systems, and the transformation between the two phases has a martensitic character. In addition to the AFM-FM transition, it has been found that the breakdown of charge and orbital ordering also leads to the magnetization jumps in the case of manganites, in general.…”
Section: Introductionmentioning
confidence: 99%
“…In manganites both phases coexist in low magnetic fields, and the broad metamagnetic transitions observed, are the result of an increasing field dependent fraction of the ferromagnetic phase within the phase-separated material. But in addition, measurements at very low temperatures (< 4 K) have revealed a surprising and beautiful effect: the observation of a discontinuous metamagnetic transition at a critical magnetic field [9,10,11]. This phenomenon, referred to as ultrasharp magnetization jumps, avalanche-like or abrupt metamagnetic transition, has puzzled the scientific community since it was first reported [12].…”
Section: -Introductionmentioning
confidence: 99%
“…This was first observed by Hebert et al 7 when the Mn sub-lattice was diluted with some magnetic or non-magnetic impurities and subsequently by Fisher et al 8 by augmenting the cation-disorder at the Asite 11 . Such low temperature metamagnetic behavior in manganite compounds is remarkable as these first order transitions display a crossover from a smooth to a sharp metamagnetic transition [7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%